تنظيم وتحفيز الاستثمار في ضوء القانون 22 - 18 لستة 2022 الصادر بالجزائر - بوزيان, يعقوب (جامعة الوادي - University of Eloued, 2024)
تهدف هذه الدراسة الى التعرف على أهداف ومبادئ قانون الاستثمار الجديد الصادر في 2022 ، كذلك التعرف على الحوافز والضمانات التي أقرها المشرع للمستثمرين ، استعملت المنهج الوصفي التحليلي ، واسلوب تحليل المحتوى في معالجة قانون الاستثمار . من نتائج هذه الدراسة أن القانون تضمن اعفاء المستثمر من الضرائب والرسوم خلال عملية الانجاز ولمدة قد تتجاوز عشر سنوات خلال عملية الاستغلال ، كذلك أقر القانون للمستثمر ضمانات تحويل الاموال وسهولة الحصول على المعلومات اللازمة لا سيما منها فرص الاستثمار في الجزائر ، والعرض العقاري والتحفيزات والمزايا المرتبطة بالاستثمار . This study aims to identify the objectives and principles of the new investment law announced in 2022, as well as to identify the guarantees and incentives approved by the legislator for investors, The analytical descriptive approach and content analysis method was conducted in this study. As a result of this investigation, the investment law included the exemption of the investor from taxes and royalties for more than ten years during the completion and exploitation process. Moreover, the law gives the investor guarantees on the money transfer and the ease of obtaining the necessary information. Also, it provides the real estate offer, the incentives and advantages related to the investment
Organization and encouragement investment in light of 2022 law , no 22- 18 in Algeria
مقال
Keywords: الاستثمار - ; الحوافز ; القانون; Investment; Incentives; Law